Public Accounts Committees in Eastern and Southern Africa: A Comparative Analysis. Issue 1 (February 2014) - Pelizzo, Riccardo; Kinyondo, Abel
<x xml:space="preserve">Abstract</x> This article provides the first and most comprehensive analysis of Public Accounts Committees (PACs) from Eastern and Southern Africa building on the work of McGee, Jacobs, Stapenhurst, and Staddon. By analyzing an original set of data, this article shows that PACs in these two regions are bigger, have more staff members, and are more likely to be chaired by opposition Members of Parliament than they have in other countries and regions. Furthermore, the data show that Eastern and Southern African PACs are more active than their counterparts elsewhere. However, lack of political will and limits to the range of powers that they enjoy as well as the dearth of quality technical support from parliamentary staff significantly undermines the effectiveness of these committees and their ability to play a greater role in curbing corruption. Related Articles <mixed-citation id="polp12062-cit-0040" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Jones</surname>, <given-names>Kate</given-names></string-name>, and <string-name><surname>Kerry</surname><given-names>Jacobs</given-names></string-name>. <year>2009</year>. " Public Accounts Committees, New Public Management, and Institutionalism: A Case Study ." <source content-type="journalTitle">Politics & Policy</source><volume>39</volume> (<issue>5</issue>): <fpage>1023</fpage>‐<lpage>1046</lpage>. http://onlinelibrary.wiley.com/doi/10.1111/j.1747‐1346.2009.00209.x/abstract</mixed-citation> <mixed-citation id="polp12062-cit-0041" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Pelizzo</surname>, <given-names>Riccardo</given-names></string-name>. <year>2010</year>. " Public Accounts Committees in the Pacific Region ." <source content-type="journalTitle">Politics & Policy</source><volume>38</volume> (<issue>1</issue>): <fpage>117</fpage>‐<lpage>137</lpage>. http://onlinelibrary.wiley.com/doi/10.1111/j.1747‐1346.2009.00231.x/abstract</mixed-citation> <mixed-citation id="polp12062-cit-0042" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Pelizzo</surname>, <given-names>Riccardo</given-names></string-name>, <string-name><surname>Rick</surname><given-names>Staphenhurst</given-names></string-name>, <string-name><surname>Vinod</surname><given-names>Sahgal</given-names></string-name>, and <string-name><surname>William</surname><given-names>Woodley</given-names></string-name>. <year>2006.</year> " What Makes Public Accounts Committees Work? A Comparative Analysis ." <source content-type="journalTitle">Politics & Policy</source><volume>34</volume> (<issue>4</issue>): <fpage>774</fpage>‐<lpage>793</lpage>. http://onlinelibrary.wiley.com/doi/10.1111/j.1747‐1346.2006.00040.x/abstract</mixed-citation> Related Media <mixed-citation id="polp12062-cit-0043" publication-type="other" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>African</surname> <given-names>Videos</given-names> </string-name>. <year>2013</year>. "<source content-type="otherTitle">Frustrated Parliamentary Public Accounts Committee Gives Up on Interrogating Geoffrey Kazinda</source>." http://www.africanvid.com/uganda/frustrated‐parliamentary‐public‐accounts‐committee‐gives‐up‐on‐interrogating‐geoffrey‐kazinda/</mixed-citation> <mixed-citation id="polp12062-cit-0044" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Mokone</surname>, <given-names>Thabo</given-names></string-name>. <year>2012</year>. " Presidency Grilled for Over‐Spending ." <source content-type="journalTitle">Sowetan Live</source>. http://www.sowetanlive.co.za/news/2012/06/14/presidency‐grilled‐for‐over‐spending</mixed-citation>